Working memory and temporal attention: Dissociating the role of cognitive preparedness and memory strategy - Tonković, Mirjana (Array, 2007)
Research in temporal attention suggests that participants use temporal information to deploy attentional resources. Is it possible to use such information to influence working memory performance? To test this hypothesis an S1– S2 paradigm was employed, in which a warning stimulus (S1- a beep) provides information on the onset of the imperative stimulus (S2 – a sentence). Previously we found significant differences in the WM capacity depending on the length of the SOA. Since it could not be dissociated whether this was due to a better cognitive preparedness (allocated attention) or to the memorization strategy deployed, our aim in the present experiment was to dissociate these effects by introducing articulatory suppression as an independent variable. Forty participants were given a standard WM task combining sentence verification and its final word recall. The experiment was a 2 (with / without warning signal) X 2 (with / without articulary suppression) within-subjects factorial design.